Nationality and work role interactions: A cultural contrast of Israeli and U.S. entrepreneurs' versus managers' needs - Baum, J.Robert; Olian, Judy D.; Erez, Miriam; Schnell, Eugene R.; Smith, Ken G.; Sims, Henry P.; Scully, Judith S.; Smith, Ken A. (Journal of Business Venturing, 1993)
The globalization of business ventures and the parallel search for sources of international competitive advantage have stimulated research relating cultural differences to entrepreneurial and managerial behaviors. Recent work by McGrath, MacMillan, and Scheinberg (1992) encouraged studies of managers and entrepreneurs in different cultures, suggesting that these comparisons may “… shed additional light into the interrelations between social structure, wealth creation, and cultural beliefs” (McGrath el at. 1992, p. 116). This study follows that advice. Cultural differences are powerful determinants of behavior, and many studies support the notion that managerial behavior must adapt to the national cultural setting to achieve success. A growing stream of entrepreneurial behavior research has explored differences in motivational needs between entrepreneurs and non-entrepreneurs of different countries, and found parallel differences across cultures. Given these views, we might expect to find need differences between entrepreneurs and managers within countries however, some entrepreneurship researchers have concluded that U.S. managers and entrepreneurs are more alike than different. To better understand need profile differences between and within cultures, we use a theory that suggests that culture is an important determinant of work behavior. The process through which culture affects work behaviors is described in “Cultural Self-representation Theory” (Erez and Earley, 1993). Based upon this theory, inferences from the entrepreneurial archetype, and analysis of the contrast between the cultures of Israel and the U.S., we propose that: (1) entrepreneurs and managers have different motivational needs within some national cultures, and (2) across national cultures there are systematic differences in motivational needs. Based on these premises, an interaction hypothesis between work role and nationality is suggested because of the importance of both culture and work role in determining motivational need differences. Data are collected from over 370 Israeli and U.S. entrepreneurs and managers. Results support cultural self-representation theory for the Israeli-U.S. and entrepreneur-manager case, because interactions between nationality and work role are exposed for various needs. This finding suggests that cultural differences are indeed important for understanding management motivational needs in different nations, and that the effectiveness of entrepreneurial approaches to management may be culture-sensitive. The study illustrates work-role differences between Israeli managers and entrepreneurs. We confirm past conclusions about U.S. entrepreneur-manager need similarities, and suggest that these need similarities are supported by the individualistic culture within U.S. organizations.